Dispersive charge transport in hopping systems under open-circuit conditions: computer simulation - Bąk, Grzegorz (Wydawnictwo Politechniki Łódzkiej, 2012)
Applicability of the theories describing the discharge in thin-film insulators under open-circuit conditions for dispersive hopping systems is the subject of this paper. It is shown by means of computer simulation that the drift mobility obtained from application of the theories for such systems is underestimated. The computer simulation was carried out for a thin film system in which the charge transport is dominated by hopping of charge carriers among localized states in a narrow band at the Fermi level. The way of interpretation of the discharge under opencircuit conditions in such systems is suggested. The simulation results have also been applied for interpretation of the open-circuit discharge in thin diamond-like carbon films.

Badano stosowalność teorii opisujących rozładowanie cienkich warstw izolatorów z przeskokowym transportem ładunku w warunkach obwodu otwartego. Pokazano, że wartości ruchliwości otrzymane w wyniku zastosowania tych teorii do układów dyspersyjnych są niedoszacowane. Symulację wykonano dla układów, w których transport przeskokowy odbywa się w wąskim paśmie w pobliżu poziomu Fermiego. Otrzymane wyniki zastosowano do reinterpretacji wyników badań ruchliwości w warstwach DLC.
Dyspersyjny transport ładunku w układach przeskokowych w warunkach obwodu otwartego: symulacja komputerowa